Modified tarsorrhaphy versus gold weight implant technique for paralytic lagophthalmos treatment in patients with leprosy: One-year observation of a randomized controlled trial study - Irawati, Yunia; Natalia, Michelle Eva Rebeca; Gondhowiardjo, Tjahjono D.; Dachlan, Ishandono; Soebono, Hardyanto (Frontiers in Medicine, 2023)
Trial design: This study was a multicenter, PROBE (Prospective Randomized Open-label Blinded-Endpoint) clinical trial, parallel-group study conducted in Indonesia (3 sites). Methods: The aim of this study is to compare the effectivity and efficiency of Modified Tarsorrhaphy (MT) technique and Gold Weight Implant (GWI) techniques as surgical treatment of paralytic lagophthalmos in leprosy patients. Samples consisted of 23 eyes, 11 eyes were in the MT group, while the other 12 eyes were in the GWI group as the control group. Results: Central eyelid margin distance (lagophthalmos distance) with gentle pressure decreased in the MT group (3.09 mm to 0.43 mm) and GWI group (3.21 mm to 0.83 mm) in 1 year postoperative. The Ocular Surface Disease Index score, Tear Break-up Time, Schirmer without and with anesthesia in the MT and GWI groups showed the p-value of >0.05. Epitheliopathy improvement occurred in 54.55% of the MT group and 58.33% of the GWI group. Corneal sensitivity change in inferior quadrant of the MT group (50.00 to 51.30 mm) and in the GWI group (49.61 to 52.93 mm) resulted in p-value > 0.05. Postoperative complication occurred in 15% patients in the GWI group. In addition, surgery duration of both techniques were similar. Furthermore, the surgery cost in the MT and GWI group yielded p-value < 0.05. Conclusion: The MT technique is as effective as the GWI technique but more efficient than GWI technique as surgical treatment for paralytic lagophthalmos in patients with leprosy. Keywords: Hansen's disease, paralytic lagophthalmos, surgical intervention, epitheliopathy, corneal exposure